WEBVTT
00:00:02.490 --> 00:00:12.740
Determine the surface area of the sphere of equation π₯ squared plus π¦ squared plus π§ squared minus 1,444 equals zero, leaving your answer in terms of π.
00:00:13.240 --> 00:00:18.560
The surface area of a sphere is given by the expression four times π times the radius of the sphere squared.
00:00:18.990 --> 00:00:23.460
So our goal will be to use the given equation for our sphere to find its radius.
00:00:23.750 --> 00:00:29.120
To do this, weβll need to transform our equation into the so-called standard form of the equation of a sphere.
00:00:29.600 --> 00:00:38.750
The standard form for the equation of a sphere is π₯ minus π₯ naught squared plus π¦ minus π¦ naught squared plus π§ minus π§ naught squared equals π squared.
00:00:39.210 --> 00:00:45.940
π₯ naught, π¦ naught, and π§ naught are the coordinates of the center of the sphere and π squared is the square of its radius.
00:00:46.170 --> 00:00:53.910
So from the equation of a sphere in standard form, we can directly read off π squared, which is the quantity we need for our surface area formula.
00:00:54.410 --> 00:00:59.280
In general, putting an equation in standard form involves completing the square for each variable.
00:00:59.650 --> 00:01:02.760
However, for our equation, this is essentially already done for us.
00:01:02.870 --> 00:01:06.560
To see why, letβs expand out the term π₯ minus π₯ naught squared.
00:01:07.070 --> 00:01:12.550
π₯ minus π₯ naught squared is π₯ squared plus two π₯ naught π₯ plus π₯ naught squared.
00:01:13.210 --> 00:01:21.330
π₯ squared is quadratic in the variable π₯, two π₯ naught π₯ is linear in the variable π₯, and π₯ naught squared is a constant.
00:01:22.010 --> 00:01:25.780
Expanding out the other two terms gives us the same sort of thing.
00:01:26.090 --> 00:01:34.260
We get a quadratic term in π¦ and a quadratic term in π§, a linear term in π¦ and a linear term in π§, and a constant term from each.
00:01:34.500 --> 00:01:38.610
Our goal is to work backwards from the expanded equation to the equation in standard form.
00:01:38.900 --> 00:01:42.030
And to do that, weβll need to find π₯ naught, π¦ naught, and π§ naught.
00:01:42.490 --> 00:01:47.790
Note that the quadratic terms donβt help us because they are unrelated to the values of π₯ naught, π¦ naught, and π§ naught.
00:01:48.090 --> 00:01:55.550
Similarly, the constant term doesnβt help because π₯ naught squared, π¦ naught squared, and π§ naught squared all act together into a single constant.
00:01:55.840 --> 00:01:58.530
However, the linear terms are exactly what we need.
00:01:58.720 --> 00:02:03.300
They donβt add across variables and they depend on the coordinates of the center of the sphere.
00:02:03.700 --> 00:02:10.280
In particular, half the coefficient of each linear term is the corresponding coordinate for the center of the sphere.
00:02:10.670 --> 00:02:18.020
However, looking back at our original equation, we have all three quadratic terms and a single constant term but no linear terms.
00:02:18.380 --> 00:02:23.170
But the only way for linear terms not to appear in this equation is if their coefficients are zero.
00:02:23.790 --> 00:02:28.740
In other words, two π₯ naught is zero, two π¦ naught is zero, and two π§ naught is zero.
00:02:29.270 --> 00:02:31.850
So π₯ naught, π¦ naught, and π§ naught are all zero.
00:02:32.240 --> 00:02:42.380
But that means that our original equation is equivalent to π₯ minus zero squared plus π¦ minus zero squared plus π§ minus zero squared minus 1,444 equals zero.
00:02:42.940 --> 00:02:49.510
But looking carefully, we see that the sum of these three terms is exactly the left-hand side of the equation of a sphere in standard form.
00:02:49.990 --> 00:02:56.500
So to finish putting this equation in standard form, all we need to do is add 1,444 to both sides.
00:02:56.880 --> 00:03:10.230
So π₯ minus zero squared plus π¦ minus zero squared plus π§ minus zero squared is equal to 1,444, from which then follows directly from the equation in standard form that π squared is 1,444.
00:03:10.770 --> 00:03:14.220
So now all we do is plug this value into the surface area formula.
00:03:14.620 --> 00:03:23.060
So we have four times π times 1,444, which in terms of π is 5,776π.
00:03:23.340 --> 00:03:41.720
Itβs worth mentioning that since π₯ minus zero squared is just π₯ squared, π¦ minus zero squared is just π¦ squared, and π§ minus zero squared is just π§ squared, we couldβve recognized at the beginning that adding 1,444 to both sides of our equation takes us directly to this equation in standard form.
00:03:41.940 --> 00:03:45.670
And so 1,444 is the square of the radius of the sphere.